2010
DOI: 10.1016/s2255-4971(15)30224-x
|View full text |Cite
|
Sign up to set email alerts
|

Total Ankle Arthroplasty: Brazilian Experience With the Hintegra Prosthesis

Abstract: Ankle arthrosis is becoming more and more common. The search for solutions that preserve joint function has led to a new generation of prosthesis with three components and more degrees of freedom. This paper presents the results achieved for ten patients treated with the HINTEGRA Prosthesis (Integra, New Deal), through collaborative action between the Foot and Ankle Groups of the Orthopedics and Traumatology divisions of Escola Paulista de Medicina, Unifesp, and the School of Medicine of the University of São … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…We selected 12 studies assessing radiographic patterns of normal ankles, and identified a total of 15 possible radiographic measurements (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected 12 studies assessing radiographic patterns of normal ankles, and identified a total of 15 possible radiographic measurements (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) .…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of ankle arthrosis includes conservative measures (drug and orthotic treatment), orthobiologic resources (5) and surgical procedures (joint debridement, arthrodiastases, supramalleolar osteotomies, en bloc autologous cartilage transplantation, total arthroplasty and ankle arthrodesis) (6)(7)(8)(9)(10)(11)(12) . Surgical treatment prognosis depends, among other factors, on the degree of joint damage, patient characteristics, and tibiotalar joint realignment (6) .…”
Section: Introductionmentioning
confidence: 99%
“…The total ROM and clin- makes it hard to compare complication rates. Complications are categorized as intraoperative and postoperative [1,3,11,13,20,25], as minor and major [18,19,26], as high grade, medium grade, and low grade [2,10,23], or are not classified at all [2,9,12,14,16]. A further issue is heterogeneity in which events are counted as complications, for example HO is sometimes mentioned as complication and sometimes as radiological outcome.…”
Section: Resultsmentioning
confidence: 99%
“…The third-generation prostheses, which comprise three elements (tibial, talar and intermediate components), have been the most successful of these so far. 77 , 78 , 79 …”
Section: Osteotomiesmentioning
confidence: 99%
“…During the postoperative period, the complications relate to dehiscence of the surgical incision and infection. 78 , 81 Over the long term, the greatest complication is aseptic loosening of the tibial or talar components, followed by stress fracturing, capsule retraction and retraction of the periarticular soft tissues. 82 …”
Section: Osteotomiesmentioning
confidence: 99%